Application of the Authority of the Constitutional Court in Resolving Disputes on Regional Head Election Results - Ahmad Shodiqin (JUSTICES: Journal of Law, 2023)
This thesis aims to determine the implementation of the provisional authority mandated to the Constitutional Court in resolving election results disputes and this research also aims to determine the impact and effectiveness of the implementation of the election settlement regulations regarding the provision of vote difference thresholds. This study used the library research research method in collaboration with observation or observation methods. The number of cases registered with the Constitutional Court was 53 cases, while only 7 cases passed and advanced to the trial process. The results of the study show that the administration is systematically structured and is still the main argument by the litigants for the sake of overriding the threshold provisions. The implementation of the authority of the Constitutional Court in resolving disputes follows substantial justice while remaining obedient to the constitution, as well as an effort to protect citizens' constitutional rights. However, on the other hand, the element of legal certainty in carrying out the mandate of the Pilkada law for the disputing parties was not fully fulfilled.